Análise de soluções desinfetantes convencionais e fitoterápicas sobre a estabilidade de cor de um silicone facial com diferentes pigmentações submetido ao envelhecimento acelerado - Paulini, Marcela Borghi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The disinfection of maxillofacial prostheses with conventional disinfecting solutions have the potential to alter the properties of the material, reducing its lifetime. The phytotherapy may be a suitable alternative to this disinfection, however, the effect of these vegetable extracts over these properties are not known. Evaluate the influence of the conventional disinfecting solutions and plant extracts as well as the accelerated aging on the color stability to a silicone to facial prosthesis. Were prepared two hundred samples (5 mm x 6 mm) of silicone facial (MDX4-4210). Two-tone pigment and opacifier were combined with silicone, yielding four groups: colorless (GI), colorless to opacifier (IGI), midtone pigment and opacifier (GIII) and dark color pigment and opacifier (GIV). The disinfection process was carried out for 30 days with the following solutions: saline; mild soap and water; 4% chlorhexidine; Hydrastis Canadensis e Cymbopogonnardus. The samples were subjected to color stability test and exposed to 1008 hours of accelerated aging (53 ATSM). Data were subjected to analysis of variance three factors (ANOVA) and Tukey test (α = .05) .The accelerated aging not only promoted color change to the GII (P> .05), regardless of disinfectant. There was a significant difference (P <. 05) between the ΔE values of samples disinfected with H. canadensis (HC), C. nardus (CN) and chlorhexidine (Ch) compared to saline water and soap. After accelerated aging, the disinfected subgroup C. nardus (CN) was statistically similar (P <.05) compared to the physiological saline and water-soap. All of silicone MDX4-4210 groups showed clinically unacceptable color changes, regardless of the use or not of disinfectant solutions. The Herbal medicine can be a viable alternative for the disinfection of maxillofacial prostheses made with silicone MDX4-4210 because this method produced color change similar to conventional disinfectant solution

A desinfecção de próteses maxilofaciais com soluções desinfetantes convencionais tem potencial para alterar as propriedades do material, reduzindo seu tempo de vida útil. A fitoterapia pode ser uma alternativa adequada para esta desinfecção, entretanto o efeito destes extratos vegetais sobre estas propriedades não é conhecido. Avaliar a influência de soluções desinfetantes convencionais e extratos de plantas, bem como do envelhecimento acelerado sobre a estabilidade de cor de um silicone para prótese facial. Duzentas amostras (5 mm x 2 mm) do silicone facial (MDX4-4210) foram confeccionadas. Duas tonalidades de pigmentos e um opacificador foram combinados com o silicone, obtendo-se quatro grupos: incolor (GI), incolor com opacificador (GII), pigmento de tonalidade média e opacificador (GIII) e pigmento de tonalidade escura e opacificador (GIV). O processo de desinfecção foi realizado durante 30 dias, com as seguintes soluções: soro fisiológico; água e sabão neutro; clorexidina 4%; Hydrastis canadensis e Cymbopogonnardus. As amostras foram submetidas ao teste de estabilidade de cor e expostas a 1008 horas de envelhecimento acelerado (ATSM 53). Os dados foram submetidos à análise de variância três fatores (ANOVA) e teste Tukey (α=.05). O envelhecimento acelerado só não promoveu alteração de cor para o grupo GII (P>.05), independente do desinfetante. Houve diferença significante (P<. 05) entre os valores de ΔE das amostras desinfetadas com H. canadensis (HC), C. nardus (CN) e clorexidina (Ch) em comparação ao soro fisiológico e água-sabão. Após o envelhecimento acelerado, o subgrupo desinfetado com C. nardus (CN) mostrou-se estatisticamente semelhante (P< 05) em relação ao soro fisiológico e água-sabão. Todos os grupos do silicone MDX4-4210 apresentaram alterações de cor clinicamente...
Keywords: Prótese maxilofacial; Silicones; Desinfecção; Fitoterapia; Maxillofacial prosthesis